2016
DOI: 10.1182/blood-2015-11-624312
|View full text |Cite
|
Sign up to set email alerts
|

Splenic marginal zone lymphoma: from genetics to management

Abstract: Splenic marginal zone lymphoma (SMZL) is a rare B-cell malignancy involving the spleen, bone marrow, and frequently the blood. SMZL lymphomagenesis involves antigen and/or superantigen stimulation and molecular deregulation of genes (NOTCH2 and KLF2) involved in the physiological differentiation of spleen marginal zone B cells. Diagnosis requires either spleen histology or, alternatively, the documentation of a typical cell morphology and immunophenotype on blood cells coupled with the detection of intrasinuso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
142
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(146 citation statements)
references
References 105 publications
4
142
0
Order By: Relevance
“…The overall age-adjusted incidence is 0.13/100,000 habitants per year. The percentage change in age-adjusted incidence is 4.81%, with most of the patients being White 8 . Gender prevalence is controversial,6, 7 but there is an increasing trend to male predominance 8, 10, 11…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations
“…The overall age-adjusted incidence is 0.13/100,000 habitants per year. The percentage change in age-adjusted incidence is 4.81%, with most of the patients being White 8 . Gender prevalence is controversial,6, 7 but there is an increasing trend to male predominance 8, 10, 11…”
Section: Epidemiologymentioning
confidence: 99%
“…There are some clinical features associated with a worse outcome such as the development of lymphadenopathy, increase in β2-microglobulin, non-hematopoietic site involvement, leukocyte count >20 × 10 9 /L, lymphocytosis >9 × 10 9 /L, lymphopenia, anemia, thrombocytopenia, use of chemotherapy, monoclonal component, performance status ≥2, incomplete response, advanced age, diffuse pattern of bone marrow infiltration and histologic transformation 8, 10, 35, 36, 37, 38…”
Section: Prognosismentioning
confidence: 99%
See 2 more Smart Citations
“…11 Peripheral blood atypical lymphocyte morphology consists of villous lymphocytes with basophilic cytoplasm. 11,12 Franco et al reported that bone marrow (BM) infiltration of the SMZL was mostly of the intrasinusoidal type and BM infiltration tended to become frankly nodular after splenoctomy. 13 On the other side, atypical neoplastic lymphocytes of our patient did not have villous projections.…”
Section: Discussionmentioning
confidence: 99%